Association between screen use at night, food consumption at dinner, and evening snack in schoolchildren aged 7 to 14 years with and without overweight, Florianópolis, Santa Catarina, Brazil - Roberto, Denise Miguel Teixeira (2024)
Objective Analyze the association between screen use at night, food consumption at dinner, and evening snack in schoolchildren with and without overweight. Methods Cross-sectional study with a probabilistic sample of 1396 schoolchildren from 7 to 14 years of age from public and private schools of Florianópolis, Santa Catarina, Brazil. Dietary intake and frequency of screen use of the previous day were obtained through the questionnaire Consumo Alimentar e Atividades Físicas de Escolares (Food Consumption and Physical Activities of Schoolchildren). The association between screen use at night (exposure) and consumption of food groups (outcome) according to weight status was assessed using multivariate logistic regression. Results At dinner, schoolchildren without overweight who used screens once had a lower chance of consuming fruits and vegetables (OR: 0.62, p=0.017) compared to those who did not use screens. In addition, those who used screens twice were more likely to consume sweets (OR: 2.01, p=0.002), and screen use three times or more was inversely associated with beans (OR: 0.24, p=0.003) and meat, eggs, and seafood (OR: 0.35, p=0.011) consumption. Overweight schoolchildren who used screens three times or more were more likely to consume ultra-processed foods and pizza/hamburger/ hot dogs (OR: 2.51, p=0.009). For the evening snack, it was observed that schoolchildren without overweight who used screens three times or more had a greater chance of consuming ultra-processed foods and pizza/ hamburger/hot dogs (OR: 8.26; p=0.016). Conclusion Overweight and non-overweight schoolchildren who used screens were more likely to consume ultra-processed foods. Schoolchildren without overweight and who use screens more often at night are less likely to consume healthy foods.